2011
DOI: 10.1080/00324728.2011.571385
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in late nineteenth-century Montreal: Geographic pathways of contagion

Abstract: In the City of Montreal, 1881, the presence of three cultural communities with different profiles of economic status makes it possible to observe the way social settings affected survival over a lifetime. Regression models show culturally determined maternal factors dominant for infants, and persistent throughout childhood. For post-neonates, children aged 1-4, and adults aged 15-59 household poverty has a comparable effect. Among adults, a gender penalty differs among the three communities. Models are improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 58 publications
4
25
0
1
Order By: Relevance
“…Out of 1,773 deaths recorded during the observation period, 73.5% were successfully linked to the corresponding census record. The linkage rate is similar to that reported in many linked-records studies of the period (Edvinsson 1995;Hautaniemi, Anderton, and Swedlund 2000;Thornton and Olson 2011). The length of time between the census and the death of an individual seems to have slightly reduced the chances of a secure match.…”
Section: Data Variables and Analytical Strategysupporting
confidence: 65%
See 2 more Smart Citations
“…Out of 1,773 deaths recorded during the observation period, 73.5% were successfully linked to the corresponding census record. The linkage rate is similar to that reported in many linked-records studies of the period (Edvinsson 1995;Hautaniemi, Anderton, and Swedlund 2000;Thornton and Olson 2011). The length of time between the census and the death of an individual seems to have slightly reduced the chances of a secure match.…”
Section: Data Variables and Analytical Strategysupporting
confidence: 65%
“…To account for this we used water supply, type of privy, and the presence of carters as controls. The two former measures were found to be significant in an earlier study on the impact of sanitation on infant mortality in the same setting (Jaadla and Puur 2016) and the effect of horses in near proximity to the residence has been demonstrated in other contexts (Morgan 2002;Thornton and Olson 2011). Previous research has also indicated the importance of individuals' geographical mobility to their subsequent chances of survival (Hautaniemi, Swedlund, and Anderton 1999;Kesztenbaum and Rosenthal 2011).…”
Section: Data Variables and Analytical Strategymentioning
confidence: 78%
See 1 more Smart Citation
“…L'interpellation est directe : elle ne concerne pas que les seules autorités publiques. Rappelons pour mémoire que la mortalité infantile (désormais MI) faisait dans une ville comme Montréal des ravages avec des taux effarants largement au-dessus de ce qu'on peut observer dans des villes comparables : autour de 300 % à Montréal et plus de 400 % dans certains quartiers de Québec (Gagné, 2004 ;Thornton et Olson, 2011). La lutte contre la MI est élevée au rang de cause nationale « sacrée » entraînant la plus grande mobilisation.…”
Section: Is Childhood Under Control ? or Programmed ? These Questionsunclassified
“…This includes pioneering work by the Princeton European Fertility project (Coale and Watkins 1986) and more recent studies taking spatial econometric approaches to investigate the spread of fertility decline (BocquetAppel and Jakobi 1998; Haines and Hacker 2011;González-Bailón and Murphy 2013;Goldstein and Klüsener 2014;Klüsener, Dribe, and Scalone 2016). However, the spatial analysis of historical mortality has thus far mainly focussed on infant mortality and described subnational mortality patterns (Ramiro-Fariñas and Sanz-Gimeno 2000; Edvinsson, Brändström, and Rogers 2001;Thorvaldsen 2002;van den Boomen 2015) or focussed on specific urban environments (Thornton and Olson 2011;Reid, Garrett, and Szreter 2016;Connor 2017). A more limited amount of cross-country analysis has also concentrated on infant mortality (Edvinsson, Garðarsdóttir, and Thorvaldsen 2008;Klüsener et al 2014).…”
Section: Introductionmentioning
confidence: 99%